Verschwörungserzählungen und ihre sprachlichen Spezifika am Beispiel der Reichsbürger. Typische Textsorten und charakteristische Lexik - Georg Schuppener (Linguistische Treffen in Wrocław)
The article begins by defining the concept of conspiracy and then provides a brief overview of the history of conspiracy narratives and the current state of research. It is noted that although there are already numerous publications on conspiracy narratives from various academic perspectives, the linguistic specifics of such narratives have so far been little studied. This is particularly true with regard to the lexis and, above all, the text types that are typical of conspiracy narratives. This article therefore examines two corpora of Reichsbürger texts in more detail. Since the ideology of the Reichsbürger is constitutively based on conspiracy narratives, texts from this milieu represent a suitable material basis. With regard to the typical text types in which conspiracy narratives occur, it can be shown that it is mainly tracts that are used by Reichsbürger to convey such narratives. Furthermore, text types that convey a clear factual orientation are preferred, while claims of alleged conspiracies only rarely appear in opinion-based texts. The producers emphasize that the statements are the truth, about which the ignorant majority of the population must be informed. A closer look at the specific lexis reveals parallels to this finding. Here, it can also be seen that the beliefs of the majority society are qualified as deception and fraud and thus contrasted with the conspiracy narratives of the Reichsbürger, which are described as truth. Overall, completely new insights can be gained with regard to the text types; in terms of lexis, the results obtained confirm the findings of other relevant studies in this area.